Ultrasonographic findings of rheumatoid arthritis patients who are in clinical remission - Hadi Karimzadeh; Mehdi Karami; Nasrin Bazgir; Mansour Karimifar; Ghasem Yadegarfar; Zohrea Mohammadzadeh (Journal of Research in Medical Sciences, 2018)
Background: The aim of this study was to recognize the findings of ultrasonography (US) in remitted rheumatic arthritis (RA) patients for detection subclinical arthritis. Materials and Methods: This descriptive study was conducted during 2016 in a rheumatology center. A total of 70 patients with remitted RA were included in the study. Sonography was performed on all 70 patients who did not show any clinical arthritis in clinical examination to find synovitis and effusion were evaluated with gray scale and hyperemia with power Doppler US. Results: Nearly 44.3% (n = 31) of our patients had positive sonography results including 20% synovitis, 21.4% hyperemia, and 18.6% (n = 13) effusion. A total of 1960 joints of 70 patients were evaluated, in which 3.2% (n = 63) of joints had positive sonography findings including 1.2% synovitis, 1.5% hyperemia, and 1.1 with effusion. Conclusion: US can diagnosis subclinical arthritis in patients with remitted RA who does not show any joint involvement in clinical examination.